Uprooting Bias in the Academy Lessons from the Field - Bisson, Linda F.; Grindstaff, Laura; Brazil-Cruz, Lisceth; Barbu, Sophie J. (Springer International Publishing : Imprint: Springer, 2022)
This open access book analyzes barriers to inclusion in academia and details ways to create a more diverse, inclusive environment. It first describes what the barriers to inclusion are and how they function within the broader society, focusing on concept of implicit bias: what it is, how it develops, and the importance of training organizational members to recognize and challenge it. It then discusses the limitations of data collection that is guided by the conventional assumption that being diverse automatically means being inclusive. Lastly, it highlights the importance of creating a collaborative, interdisciplinary and institution-wide vision of an inclusive community.